Combining reverse genetics and nuclear magnetic resonance‐based metabolomics unravels trypanosome‐specific metabolic pathways. Issue 5 (7th April 2015) - Bringaud, Frédéric; Biran, Marc; Millerioux, Yoann; Wargnies, Marion; Allmann, Stefan; Mazet, Muriel
Summary Numerous eukaryotes have developed specific metabolic traits that are not present in extensively studied model organisms. For instance, the procyclic insect form of Trypanosoma brucei, a parasite responsible for sleeping sickness in its mammalian‐specific bloodstream form, metabolizes glucose into excreted succinate and acetate through pathways with unique features. Succinate is primarily produced from glucose‐derived phosphoenolpyruvate in peroxisome‐like organelles, also known as glycosomes, by a soluble NADH‐dependent fumarate reductase only described in trypanosomes so far. Acetate is produced in the mitochondrion of the parasite from acetyl‐CoA by a CoA‐transferase, which forms an ATP‐producing cycle with succinyl‐CoA synthetase. The role of this cycle in ATP production was recently demonstrated in procyclic trypanosomes and has only been proposed so far for anaerobic organisms, in addition to trypanosomatids. We review how nuclear magnetic resonance spectrometry can be used to analyze the metabolic network perturbed by deletion (knockout) or downregulation (RNAi) of the candidate genes involved in these two particular metabolic pathways of procyclic trypanosomes. The role of succinate and acetate production in trypanosomes is discussed, as well as the connections between the succinate and acetate branches, which increase the metabolic flexibility probably required by the parasite to deal with environmental changes such as oxidative stress.